Global fragments : (dis)orientation in the new world order - Bartels, Anke; Wiemann, Dirk (Cross/cultures ;, 2007)
While the world seems to be getting ever smaller and globalization has become the ubiquitous buzz-word, regionalism and fragmentation also abound. This might be due to the fact that, far from being the alleged production of cultural homogeneity, the global is constantly re-defined and altered through the local. This tension, pervading much of contemporary culture, has an obvious special relevance for the new varieties of English and the literature published in English world-wide. Postcolonial literatures exist at the interface of English as a hegemonic medium and its many national, regional an.